2022
DOI: 10.1021/acsomega.2c01033
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Biosensors Based on Functionalized and Nanostructured Solitary Materials: Detection of Viral Infections and Other Risks

Abstract: Advances in nanotechnology over the past decade have emerged as a substitute for conventional therapies and have facilitated the development of economically viable biosensors. Next-generation biosensors can play a significant role in curbing the spread of various viruses, including HCoV-2, and controlling morbidity and mortality. Pertaining to the impact of the current pandemic, there is a need for point-of-care biosensor-based testing as a detection method to accelerate the detection process. Integrating bios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 134 publications
0
10
0
Order By: Relevance
“…Recent studies have confirmed that peptide-f-NPs have effective potential in antitumor nanomedicines, drug delivery in the central nervous system (CNS)-tuberculosis (TB) treatment, drug delivery, , nanobiosensors, nanovaccines, gene therapy, cancer, and many other diseases (Figure ). Regardless, the application diversity has urged researchers to explore other rationales for designing peptide-f-NPs for possible areas of improvisation.…”
Section: Biomedical Applications Of Nanopeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have confirmed that peptide-f-NPs have effective potential in antitumor nanomedicines, drug delivery in the central nervous system (CNS)-tuberculosis (TB) treatment, drug delivery, , nanobiosensors, nanovaccines, gene therapy, cancer, and many other diseases (Figure ). Regardless, the application diversity has urged researchers to explore other rationales for designing peptide-f-NPs for possible areas of improvisation.…”
Section: Biomedical Applications Of Nanopeptidesmentioning
confidence: 99%
“…Cancer, being a worldwide incurable terminal disease, creates a global demand for the creation of new materials that show features such as biocompatibility, minimum toxicity, bioavailability, etc. The universe of NPs provides a wide range of materials, among which peptide-functionalized NPs (peptide-f-NPs) has been one of the ideal biomolecules that enhance the efficiency of drug delivery, 13 , 14 biosensors, 15 COVID-19 vaccines, 16 biotemplated NP catalysts, 17 active ingredients of personal care items (toothpaste and hair coloring), 18 gene therapy, 19 and many other biomedical applications. 20 Consequently, the diverse implementation has urged researchers to explore the in situ construction of in vivo self-assembly that can be used to develop peptide-f-NPs and determine the possible areas of improvisation.…”
Section: Introductionmentioning
confidence: 99%
“…Biosensors are often functionalized to enhance their performance (sensitivity, selectivity, response time, etc.) [ 210 , 211 , 212 , 213 ] and biocompatibility [ 214 ]. Much attention has been given to the differential toxicity of functionalized carbon nanomaterials.…”
Section: Factors Affecting Toxicitymentioning
confidence: 99%
“…Due to the expanded surface area and unique surface properties, nanostructured materials have also found applications in photo- and electrocatalysis [ 92 , 115 , 116 ]. In addition, various modern sensors and biosensors were produced on their basis [ 59 , 117 ]. There are many other new applications of nanostructured materials, and almost every day we can find in the literature some new applications and devices based on them.…”
Section: Introductionmentioning
confidence: 99%